PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TERPADU SEKOLAH DASAR - Sari, Rahmi Novita; Zuraida, Zuraida; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
THE INFLUENCE OF AUDIO VISUAL MEDIA ON STUDENT LEARNING OUTCOMES IN INTEGRATED THEMATIC LEARNING IN ELEMENTARY SCHOOLAbstractThis study aims to determine the effect of audio visual media on the results of integrated thematic learning students in elementary schools. This type of research is a quasi-experimental research with non equivalent control group design. With cluster random sampling technique, obtained samples in this study, namely IVA class and IVB class SDN 01 Baringin Anam. Data collection technique use test. Hypothesis testing in this study using the t-test formula. Based of the calculation of the t-test for the posttest value, obtained tcount equal to 2,218 and ttable with the significance level of 95% (α = 0.05) equal to 1,70, then tcount > ttable. This means that there is a significant effect on the result of students’ thematic learning using audio visual media.Keyword : audio visual media, video, integrated thematic, learning outcomes